Combined exposure to PM2.5 and PM10 in reductions of physiological development among preterm birth: a retrospective study from 2014 to 2017 in China - Hu, Bo; Tang, Jie; Xu, Guangtao; Shao, Dongliang; Huang, Huafei; Li, Jintong; Chen, Huan; Chen, Jie; Zhu, Liangjin; Chen, Shipiao; Shen, Bin; Jin, Limin; et al. (Frontiers in Public Health, 2023)
Preterm birth (PTB) has been linked with ambient particulate matter (PM) exposure.However, data are limited between physiological development of PTB and PM exposure.Trimester and season-specific PM exposure including PM 2.5 and PM 10 was collected from Jiaxing between January 2014 and December 2017. Information about parents and 3054 PTB (gestational age < 37 weeks) outcomes such as weight (g), head circumference (cm), chest circumference (cm), height (cm) and Apgar 5 score were obtained from birth records. We used generalized linear models to assess the relationship between PTB physiological developmental indices and PM 2.5 , PM 10 and their combined exposures. A binary logistic regression model was performed to assess the association between exposures and low birth weight (LBW, < 2,500 g). Results showed that there were 75.5% of low birth weight (LBW) infants in PTB. Decreased PM 2.5 and PM 10 levels were found in Jiaxing from 2014 to 2017, with a higher PM 10 level than PM 2.5 each year. During the entire pregnancy, the highest median concentration of PM 2.5 and PM 10 was in winter (61.65 ± 0.24 vs 91.65 ± 0.29 μg/m 3 ) followed by autumn, spring and summer, with statistical differences in trimester-specific stages. After adjusting for several potential factors, we found a 10 μg/m 3 increase in joint exposure of PM 2.5 and PM 10 during the entire pregnancy associated with reduced 0.02 week (95%CI: -0.05, -0.01) in gestational age, 7.9 g (95%CI: -13.71, -2.28) in birth weight, 0.8 cm in height (95%CI: -0.16, -0.02), 0.05 cm (95%CI: -0.08, -0.01) in head circumference, and 0.3 (95%CI: -0.04, -0.02) in Apgar 5 score, except for the chest circumference.Trimester-specific exposure of PM 2.5 and PM 10 sometimes showed an opposite effect on Additionally, PM 2.5 (OR = 1.37, 95%CI: 1.11, 1.68) was correlated with LBW. Findings in this study suggest a combined impact of fine particulate matter exposure on neonatal development, which adds to the current understanding of PTB risk and health.